2010
DOI: 10.1016/j.ab.2010.04.033
|View full text |Cite
|
Sign up to set email alerts
|

A continuous kinetic assay for adenylation enzyme activity and inhibition

Abstract: Adenylation/adenylate-forming enzymes catalyze the activation of a carboxylic acid at the expense of ATP to form an acyl-adenylate intermediate and pyrophosphate (PP i ). In a second half-reaction, adenylation enzymes catalyze the transfer of the acyl moiety of the acyl-adenylate onto an acceptor molecule, which can be either a protein or a small molecule. We describe the design, development, and validation of a coupled continuous spectrophotometric assay for adenylation enzymes that employs hydroxylamine as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(159 citation statements)
references
References 38 publications
5
151
0
3
Order By: Relevance
“…43,44 These experiments were conducted by varying a single substrate and holding remaining reaction components at a constant saturating level in the presence and absence of inhibitor. The resulting double reciprocal (Lineweaver-Burk) plots confirmed that kinetic parameters closely matched previously reported values for both enzymes against varied citrate concentrations (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…43,44 These experiments were conducted by varying a single substrate and holding remaining reaction components at a constant saturating level in the presence and absence of inhibitor. The resulting double reciprocal (Lineweaver-Burk) plots confirmed that kinetic parameters closely matched previously reported values for both enzymes against varied citrate concentrations (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this, ATP turnover from synthetase activity was monitored using an enzyme-coupled assay involving conversion of the reporter molecule MESG to its purine base (44,45). This assay was used to empirically establish saturating levels of spermidine, ATP, and Mg 2ϩ for AsbA to determine reaction rates dependent exclusively on citric acid.…”
Section: Resultsmentioning
confidence: 99%
“…2-Amino-6-mercapto-7-methylpurine Ribonucleoside (MESG) Continuous Pyrophosphate Detection Assay-Reactions were a modification of a previously described protocol (44,45). For kinetics reactions, standard conditions were 50 mM Tris, pH 8.0, 15 mM MgCl 2 , 0.5 mM tris(2-carboxyethyl) phosphine, 6 mM ATP, 40 mM spermidine, 0.001 units/l purine nucleoside phosphorylase, 0.0004 units/l inorganic pyrophosphatase, 0.4 mM MESG (Berry and Associates, Dexter, MI), and 0.2 M purified enzyme.…”
Section: Metabolite Analysis By Tandem Mass Spectrometry (Ms/ms)-enzymentioning
confidence: 99%
“…TycB1 is derived from the tyrocidine biosynthetic enzymes, incorporates l -Pro, and contains the domain structure C-A ( l -Pro)-T. 18 Apparent K i values were determined by a coupled hydroxamate-MesG continuous spectrophotometric assay (Figure S1). 19 Probes 1 and 2 exhibited tight-binding properties against the A domains of GrsA and TycB 1 , respectively, with calculated K i app values of 1.43 ± 0.19 nM for GrsA and 327 ± 17.0 nM for TycB1 (Figure S2). Inhibitors 4 and 5 gave K i app values of 1.20 ± 0.14 nM for GrsA 16 and 431 ± 42.0 nM for TycB1, respectively (Figure S2).…”
mentioning
confidence: 99%